The Effectiveness Of Interactive Approach To Teach Reading Comprehension To First Semester Students Of STIE Nganjuk - Triana Wuri Cahyanti (STKIP PGRI Nganjuk, 2021)
The objective of the study is to investigate whether the students who is taught using interactive approach have better achievement in reading comprehension than the students who is taught by using conventional technique. This research used experimental design. The study is carried out in popuulation of students of STIE Nganjuk. It means the researcher has English for Specific Purposes (ESP) class. The result of the research is to measure the effects interactive approach has on students’ reading comprehension because they are as non-English Department learners. From the comparison of absolute gain scores between experimental group and control group, it can be concluded that the students of the experimental group have already been more proficient in dealing with the reading text because they are given interactive reading approach which has appropriate emphasis on the bottom-up and the top-down processing. Besides, while teaching them the researcher also found that the students were more attracted and motivated in learning reading when the researcher used interactive approach.